Role of emotion regulation capacities in affective state among Chinese high school students in the post-pandemic era of COVID-19 - Wang, Suyan; Chu, Yuying; Dai, Hongliang (Frontiers in Psychology, 2022)
Objective: Psychological well-being and emotion regulation skills of the vulnerable adolescents have been severely threatened by the long-term impact of the on-going COVID-19 pandemic. The aim of this study was to seek out the potentially effective emotion regulation strategies to minimize the mental health risk of the adolescents during the COVID-19 post-pandemic era. Methods: A total of 436 high school students aged 16.07±1.08 years were included in this cross-sectional study to complete questionnaires to self-report socio-demographic information, positive and negative affect state, and emotional regulation abilities. Student’s t test and one-way analysis of variance (ANOVA) were used for intergroup comparisons among socio-demographic variables. Pearson correlation analysis was used for evaluation the association between each emotion regulation strategy and positivity or negativity. Multiple stepwise linear regression analysis was used for determination of the predictors for adolescents’ positivity and negativity. Results: Adolescents’ affect was influenced by multiple emotion regulation strategies, including cognitive reappraisal, acceptance and engagement, and difficulty in awareness, acceptance, and modification of emotions after adjusting for a range of socio-demographic variables. Conclusion: Overall, our findings highlight the importance of emotional regulation strategies in modulation of mental health of the vulnerable youth population in China during COVID-19 crisis. In view of the continuous, multifaceted influence on adolescents’ mental health of the on-going pandemic, more effort should be made to leverage emotion regulation strategies to benefit their coping abilities.